أنواع محبطات الأعمال الواردة في السنة النبوية: Types of Business Discouragements Mentioned in the Prophetic Sunnah - Muhammad Farhan Salim; Yasir bin Abdillah Al-Salman (البصيرة: مجلة الدراسات الإسلامية, 2025)
This is a brief research on the types of nullification mentioned in the prophetic texts, and I named it: "Types of nullifications mentioned in the prophetic Sunnahs." It aims to explain the concept of nullification, and some related terms such as non-acceptance and invalidity. The research consists of an introduction, three chapters, and a conclusion. As for the introduction, it contains the importance of the research, its problems, objectives, and limits. Then the first chapter discusses the concept of nullification, and the second chapter discusses the types of nullification mentioned in the prophetic Sunnah, then the third chapter discusses the paths of scholars in explaining the meaning of nullification of work, then the conclusion, which includes the most important results of the research. In this research, I will follow the inductive, analytical, and critical approach, so that I will track the hadiths from the books of Sunnah, then analyze them through the research topic by looking at the nullifying work, then talk about these hadiths, and judge them according to the approach of the hadith scholars. Among the most important results of the research: Reporting that the nullifications mentioned in the Sunnah are divided into general and partial, including that the nullifications are specific to major sins, and including the clarification that the correct approach requires the correct understanding of the pure Sunnah.